The Influence of Perceived Price, Brand Trust and Quality Products Against Consumer Satisfaction At Pizza Hut Restaurant Jatiwaringin - Deniza Dwi Andrea; Sinthon L. Siahaan (Formosa Journal of Multidisciplinary Research, 2023)
This study aims to determine the effect of perceived price, brand trust, and product quality on customer satisfaction at the Pizza Hut Jatiwaringin restaurant during the period March-April 2023. The data collection for this research was by means of the survey method by distributing questionnaires that had been tested with validity and reliability tests. to customers who have visited Pizza Hut Jatiwaringin more than once. The number of samples used in this study were 200 questionnaires. Data processing carried out in this study used the SmartPLS application version 3.2.9. The results of this study are that perceived price, brand trust, and product quality have a positive and significant effect on customer satisfaction.